MULTIDRUG RESISTANCE OF Klebsiella pneumoniae IN CATS IN BOGOR, INDONESIA - Juliadi Ramadhan; Safika Safika; Ni Luh Putu Ika Mayasari (Jurnal Kedokteran Hewan, 2021)
This study aims to measure the level of antibiotic resistance to Klebsiella pneumoniae isolated from clinical cats in Bogor. Samples were isolated and identified macroscopically, microscopically, and biochemically. Positive isolates were tested for antibiotic sensitivity using the Kirby-Bauer disk diffusion method. The results showed that Klebsiella pneumoniae isolated from sputum and laryngeal swabs of clinic cats in Bogor had experienced Multidrug Resistance (MDR). The highest level of resistance to Klebsiella pneumoniae occurred in the β-lactam group (amphicillin 76%) followed by the tetracycline group (oxytetracycline 72% and tetracycline 68%), then the quinolone group (enrofloxacin 52%), and finally the aminoglycoside group (gentamicin 44%). The results of this study are expected to be taken into consideration in the use of antibiotics for the treatment of cases related to the Klebsiella pneumoniae bacteria.